2003
DOI: 10.1074/jbc.m209274200
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of Extracellular Signal-regulated Kinase 1 and 2 in Encystation of a Primitive Eukaryote, Giardia lamblia

Abstract: Mitogen-activated protein kinase (MAPK) pathways are major signaling systems by which eukaryotic cells convert environmental cues to intracellular events such as proliferation and differentiation. We have identified Giardia lamblia homologues of two members of the MAPK family ERK1 and ERK2. Functional characterization of giardial ERK1 and ERK2 revealed that both kinases were expressed in trophozoites and encysting cells as 44-and 41-kDa polypeptides, respectively, and were catalytically active. Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 42 publications
3
53
2
1
Order By: Relevance
“…In Giardia trophozoites, gPP2A-C localizes to the eight basal bodies, as previously reported for giardial PKAc/r, the MAP kinase ERK1, centrin, and calmodulin [7][8][9]24,38,39]. gPP2A-C also localizes to the ventral disk (similar to ERK 1 [9]), to the anterior and caudal PDR (similar to PKAc/r [7,8]) and to the posterior-lateral PDR (similar to centrin [24]).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In Giardia trophozoites, gPP2A-C localizes to the eight basal bodies, as previously reported for giardial PKAc/r, the MAP kinase ERK1, centrin, and calmodulin [7][8][9]24,38,39]. gPP2A-C also localizes to the ventral disk (similar to ERK 1 [9]), to the anterior and caudal PDR (similar to PKAc/r [7,8]) and to the posterior-lateral PDR (similar to centrin [24]).…”
Section: Discussionsupporting
confidence: 81%
“…Nonetheless, the signal transduction pathways leading to the cytoskeletal changes during differentiation are largely unknown. Previously, it was shown that protein kinase A (PKA) and calmodulin both localize to the Giardia cytoskeleton and regulate different steps in the resumption of motility and cytokinesis during the cellular awakening of excystation [7], while PKA and ERK kinases have been implicated in encystation [8,9]. These data suggest that specific cell signaling mechanisms may regulate cytoskeletal functions during differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Parasite, 2009, 16, 247-258 Transcription factor mSREBP translocates to the nucleus where it interacts with genomic SRE at gene promoters of either the cholesterol biosynthesis pathway (HMGCoAsyn and HMGCoA-red) and fatty acid biosynthesis (LDLr) and CWPs resulting in their up-regulation (Worgall et al, 2004;Ellis et al, 2003) (Fig. 3).…”
Section: Mise Au Pointmentioning
confidence: 99%
“…The transcriptional activity of mSREBP is decreased by its ubiquitylation and/or sumoylation while the effect of its phosphorylation depends on the kinase involved: extracellular-signal regulated kinase (ERK)-mediated phosphorylation increases transcription by mSREBP while it decreases by PKA or glycogen synthase kinase (GSK)-mediated phosphorylation (Arito et al, 2008). Giardial homologues of the mitogen-activated protein kinases (MAPKs) ERK1 and ERK2 have been identified (Ellis et al, 2003). Endogenous ERK1 exhibited increased activity, slightly higher phosphorylation and a noticeable partial relocalization to the cell membrane at an early time post-encystation induction (≈ 2 hrs; see Figs.…”
Section: Cell Signaling In Giardial Encystation: Experimental and Biomentioning
confidence: 99%
See 1 more Smart Citation